Protein Insufficiency Among First-Trimester Pregnant Women in Jambi, Indonesia - Herlambang Herlambang; Anggelia Puspasari; Citra Maharani; Rina Nofri Enis; Amelia Dwi Fitri; Erny Kusdiyah; Ismi Nurwaqiah Ibnu (Althea Medical Journal)
Background: Insufficient protein intake or specific patterns of plasma amino acid levels during pregnancy has been associated with adverse maternal and neonatal outcomes. Studies in non-pregnant women have reported an association between protein intake and amino acid levels, however, data in pregnant women remain limited. Jambi, a region rich in freshwater fish, has a traditional dishes based on fish, which may affect maternal protein adequacy. This study aimed to assess protein sufficiency intake, plasma essential amino acid levels, and the relationship between fish consumption and protein intake among first-trimester pregnant women.